Ring, Patrick 2. Recording of Ring playing traditional accordion music. - Carroll, Kayla (2013)
Patrick Ring plays accordion music. He is joined by his great-nephew, Scott Ring, who plays tin whistle. 17 songs are recorded on three separate audio files, part 2.